ORGANISATIONAL CULTURE AND INFORMATION TECHNOLOGY PROJECTS SUCCESS: THE ROLE OF PARTICIPATORY PLANNING AND ORGANISATIONAL COMMITMENT - Morgan , Asena; Kidombo , Prof. Harriet (IJRDO - Journal of Business Management, 2022)
Organizational culture is an important factor to the success of a project. Organizational culture offers a theoretical perspective on the people-centered management of an organization. It focuses on the intangible nature of an organization, encompassing organizational behaviour and the formal structures and practices in an organization. Success of organisations depends on the organizational culture.This paper discusses organizational culture and presents a model for managing cultural change in order to foster an organizational climate conducive to the successful implementation of information technology systems participatory planning playing a key role.